Correlating testosterone and fighting in male participants in judo contests - Salvadora, A.; Suay, F.; Martinez-Sanchis, S.; Simon, V. M.; Brain, P. F. (Physiology & Behavior, 1999)
The role of hormones in human aggression is open to debate, but takes on a new urgency owing to the alarming abuse of androgenic anabolic steroids by some sports participants. In this study, video-taped behavior exhibited by 28 male competitors during a judo fight was assessed to analyze its relation to serum testosterone and cortisol levels measured before and after the bouts. A positive relation between testosterone and offensive behaviors was obtained in the sense that the greater the hormonal titer, the greater the number of threats, fights, and attacks. These findings coincide with the pattern of relationships found using observational scales. Conversely, cortisol also presented positive correlations with some of these behavioral categories but did not moderate the relationship between testosterone and competitive behavior. The present results corroborate and extend earlier findings on the role of these hormones in human behavior, giving support to the view that testosterone can be linked to the expression of competitive aggression.